Missionary families : Race, gender and generation on the spiritual frontier - Manktelow, Emily J. (Book collections on Project MUSE., 2013)
Argues for the significance of missionaries' familial relations in the philosophy, conduct, and outcomes of mission work during the 19th century, using both personal writings of individual missionaries and the institutional records of the London Missionary Society to show the effect of missionaries' personal lives on the history of Christian missions.